Protected areas within rangelands globally with country boundaries - Getahun, Yasin; Flintan, Fiona E. (International Livestock Research Institute, 2018)
This map shows terristrial protected areas found within rangelands. The information on protected areas is taken from IUCN and UNEP-WCMC World Database on Protected Areas. The mapping of the rangelands is taken from rangeland types and boundaries previously mapped by University of Idaho and the Society for Rangeland Management (SRM). Country boundaries were taken from ESRI 2016.